LARANGAN BURQA DI PRANCIS KONTESTASI ANTARA KEBEBASAN BERAGAMA DAN SEKULARISME NEGARA - Putri Wahyuningtyas , Amanda; Winoto, Nadhifa Zalfa; Masrur, Muhamad (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2025)
This research explores the burqa ban as a form of state control over religious symbols and its conflict with the right to religious freedom, which is protected by international law and Islamic teachings. Using a multidisciplinary approach, the study draws on Islamic studies, sociology, anthropology, history, law, and philosophy. It examines the burqa as both a religious obligation and a cultural identity marker, while also analyzing the roots of French secularism and the philosophical debate between individual freedom and state authority. The findings reveal that France's burqa ban reflects a secular, yet discriminatory policy targeting Muslims. While some view the burqa as an act of religious devotion, the state perceives it as a threat to national unity. This clash highlights growing tensions between religious expression and secular values. To promote justice in a pluralistic society, the study suggests adopting policies that respect religious and cultural diversity.